Nowa ewangelizacja w epoce postmodernizmu i jej implikacje pastoralno-kate- chetyczne - Jacek Wojeński (Wrocławski Przegląd Teologiczny)
The new evangelization constitutes new pedagogy of the gospel truth transmission taking new methods into account, forms and means of reaching contemporary cultures and the contemporary man. Deepened reflection over the pre-evangelization and the evangelization turns out to be equally important in order to understand current efforts of the Church in handing over the Gospel. How the current analyses prove the contemporary man is longing for God’s truth and love searching for the foundation for his life. He wants to build his life and the Christian identity on the one which isn’t undergoing a change – Jesus Christ. From here the new evangelization would be a reply to challenges of the today which are of anthropological and social-cultural and religious-church nature.